Analisis Permasalahan Belajar Matematika Siswa SD Negeri Cikampek Kota - Oktavia Sukmana (Pusat Riset dan Inovasi Nasional, 2024)
Mathematics learning in SD Negeri Cikampek Kota faces several complex issues, including irrelevant curriculum, low teaching quality, low student interest and motivation, and limited resources. To address these problems, integrated actions from various stakeholders are needed. Recommended actions include refining a more relevant and integrative mathematics curriculum, enhancing teaching quality through teacher training and mentoring, utilizing technology in learning, boosting student motivation, involving parents and the community, and developing collaborative learning approaches. By implementing these strategies holistically and sustainably, it is hoped that the understanding and achievement of mathematics among students in SD Negeri Cikampek Kota can be improved. Ongoing evaluation and feedback are also necessary to ensure the success of improvement efforts. Thus, mathematics learning in SD Negeri Cikampek Kota is expected to become more effective and competitive, in line with national education goals.